Penerapan Manajemen Keselamatan Pasien dalam Usaha Pencegahan Kejadian Pasien Jatuh di Rumah Sakit Islam Klaten - Supriyadi, Pramudio Bagus, Dr. Heru Subaris Kasjono, SKM., M.Kes, Kusuma Estu Werdani, SKM., M.Kes (2017)
The incident of patients fall has happened in Islam Hospital of Klaten. The incident of patients fall is one the measure of patient safety standard. Islam Hospital of Klaten actually has been had the management of patient safety on prevented the patients fall. Existence incident of patients fall will cause losses for both the patient and the hospital. This study aim to evaluate the implementation of patient safety management on prevented the patient fall at Islam Hospital of Klaten referred to seven step towards patient safety. The type and design of this study is a qualitative study with critical incident approach. The informant in this study consists of three main informants and one informant triangulation with purposive sampling technique in determining the informants. The results of this study showed that the implementation of patient safety management on prevented the patients fall at Islam Hospital of Klaten referred to seven step towards patient safety has already performed well. However, there are weakness of the difference attention the hospital officer to the patient fall low risk and patient fall high risk, not repeated education to family or patients about of patients fall risk and the absence of reported the incident from PMKP committee to KNKP-RS. It can be advised that should have been equalisation attention of the hospital officer to the patient fall low risk and patient fall high risk, repeated education to family or patients about of patients fall risk until them understand, and should have been reported the incident from PMKP committee to KNKP-RS according regulations.